All functions have an inverse expression.
From the question, we have the following observations:
So, the cost function would be:
[tex]\mathbf{C(x) = 50000 + (x - 100) \times 100}[/tex]
Where: x represents the number of guests, and C(x) represents the cost function
Expand
[tex]\mathbf{C(x) = 50000 + 100x - 10000}[/tex]
Evaluate like terms
[tex]\mathbf{C(x) = 40000 + 100x}[/tex]
To calculate the inverse function, we have:
[tex]\mathbf{C(x) = 40000 + 100x}[/tex]
Replace C(x) with y
[tex]\mathbf{y = 40000 + 100x}[/tex]
Swap x and y
[tex]\mathbf{x = 40000 + 100y}[/tex]
Subtract 40000 from both sides
[tex]\mathbf{x - 40000 = 100y}[/tex]
Divide both sides by 100
[tex]\mathbf{\frac{x - 40000}{100} = y}[/tex]
Rewrite as:
[tex]\mathbf{y= \frac{x - 40000}{100} }[/tex]
Split
[tex]\mathbf{y= \frac{x}{100} - \frac{40000}{100} }[/tex]
[tex]\mathbf{y= 0.01x - 400 }[/tex]
Hence, the inverse function is: [tex]\mathbf{C'(x) = 0.01x - 400 }[/tex]
Read more about functions and inverse at:
https://brainly.com/question/10300045